Cultured meat, clean meat,… queer meat? A vegan queer ecofeminist perspective on the implications of cellular agriculture - Jiménez Rodríguez, Adriana (Frontiers in Sustainable Food Systems, 2023)
This perspective article briefly explores the social implications of cellular agriculture from a Vegan Queer Ecofeminist point of view by referring to a synthesis of currently agreed-upon (possible) positive and negative effects of post-animal agriculture and highlighting how these effects actually ignore key ethical problems inherent in animal agriculture itself. By invisibilizing these, discussions of cellular-ag remain in danger of obscuring the ways in which an intact and unexamined paradigm based on capitalist, patriarchal speciesism will continue to foment exploitative and unjust practices in a dying planet. The article emphasizes the urgent need to address the complexities of cellular-ag from a multidisciplinary perspective that actively engages with the demands of true global justice for all, nonhuman and human.